تقييم التشكيلات الجيولوجية الهامة نفطيا في حوض الدو- سورية (Latakia University Journal -Basic Sciences Series, 2014)
حددت التشكيلات الرسوبية في حوض الدو اعتمادا على المستحاثات أو بالمضاهاة الطبقية في حال غياب المستحاثات. تبين نتيجة معاملة المعطيات الجيولوجية لحوض الدو وتحليل المتتاليات الليتولوجية فيه، أن أهم الصخور المولدة للنفط والغاز تابعة للسيلوري والترياسي الأسفل بينما لا تمثل رسوبيات الجوراسي أهمية توليدية, أما رسوبيات الكريتاسي الأعلى فليس لها أهمية توليدية لقربها من السطح واجتياحها من قبل المياه السطحية. تتمثل الصخور الخازنة بتشكيلات مرقدة، كوراشينا دولوميت ، بوطما ، رطبة وجديا . تمثل تشكيلات التنف، أمانوس شيل، وكوراشينا أنهدريت صخورا غطائية جيدة للصخور الخازنة في حوض الدو، كما أن غياب بعض التشكيلات الغطائية يقلل من أهمية بعض التشكيلا ت الخزنية في الحوض. أكدت هذه الدراسة أن سرعة معدل الهبوط التدريجي للحوض أدى لزيادة سماكة التشكيلات ومن ثم زيادة مأموليتها بشكل عام. Sedimentary Formations in Al'Daww Depression has been determined on fossils or strata correlation on upcent of fossils. We found from geological data  processing and analysis of litho logical series to Al'Daww Depression that the important rocks  that generated  oil and gas are belong to Silurian and lower Triassic where as Jurassic sediment does not represent any important, nor  upper Cretaceous sediments because its adjacent to surface and invaded by surface water. Reservoir rocks represented by Markada's Kurashina Dolomite, Butma, Rutba and Judea formations. The good cover rocks represented by the Tanf, Amanous Shale and Kurrachina Anhydrite 13 as well as the upcent of some cover formations deteriorated  the important of some reservoir  formations at Al'Daww Depression This study reveal that the subsiding velocity rate to the basin produced the thickness' and made this formations more prospective in general.